indonesia - Filialdi Nur Hidayat; Ferliana Widyasari; Ikha Jayanti Mamayu Utami; Mesti Putri Afandi; Santoso Budi Widiarto; Rosmini Rosmini (Jurnal Airaha, 2017)
Kima has nine species, and seven species are found in Indonesian waters. Morella Sea waters, District Leihiitu, Central Maluku is an area that has the potential of marine biodiversity and high resources which one is kima. To maintain and preserve the habitat of Kima, the government through the Ministry of Marine Affairs and Fisheries declared the Making of Kima Garden in these waters. The purpose of this research survey is to know the acceptance of the community related to the manufacture of Kima Garden in Tanjung Setan, Negeri Morella, Leihiitu District, Central Maluku. Based on the results of the survey, the perception of the community about the making of kima garden is very positive, besides that more role of the government will have an impact to increase the community participation about the making of the Kima Garden in Negeri Morella.